Investigation and failure analysis of a diesel generator connecting rod - Wilarso Wilarso; Che Wan Mohd Noor; Ahmad Faisal Mohamad Ayob; Wan Nurdiyana Wan Mansor (Mechanical Engineering for Society and Industry, 2022)
This article reports a failure analysis of a diesel generator set connecting rod type 3516 B that has operated for 79,678 hours. From visual observation, connecting rod cylinder #10 has changed color in the shank area. This phenomenon may represent many cases of generator failure, so an analysis to identify the root cause of the failure is needed for scientific literature. In this case, fault tree analysis, SEM-EDX, chemical composition, and microstructure testing were performed to obtain more comprehensive results. Through fault tree analysis, we found that the connecting rod damage was caused by compression leakage due to wear on the cylinder liner. Scanning Electron Microscopy (SEM) analysis shows that the piston rod material is discolored due to heat, namely the formation of iron oxide. The heat level received by the connecting rod is around 200 °C. We also found a finely formed, easy-to-clean scale where the thickness ranged from 0.00127–0.008 mm. Finally, EDX analysis showed high levels of iron (Fe) and oxygen (O) confirming that the formation of iron-oxide on the metal surface was due to the influence of heat.